Effect Of Problem-Based Learning Media Teaching Edugame To Improve Science Literacy And Collaboration Solar System Material - Sumarsih, Sumarsih; Parmin, Parmin; Masduki , Lusi Rachmiazasi (Jurnal Elementaria Edukasia, 2024)
Innovative and interesting approach to learning is a learning innovation in the delivery of material to students. One method that is being developed is the use of technology-based educational media packaged in the form of educational games or so-called edugames. The purpose of this study is to describe and analyse the implementation of edugame learning media with PBL method in improving students' scientific literacy and learning outcomes. This study uses pre-experimental with the research design used is a group pretest-posttest design. This study was conducted in Cabak Primary School, Jiken District, Blora Regency, with the subject of research consisting of students of class V. The research sample was selected by purposive sampling, namely class V consisting of 60 students, divided into two classes, namely class A and class B, each consisting of 30 students. Data analysis was done using t-test and measuring instruments to measure the students' ability on the Solar System material using the Problem Based Learning method. The results of this study showed a significant improvement in students' grades, which reflected not only an improvement in academic results but also a positive change in the liveliness aspect of learning. Conclusion The use of active and innovative learning methods can improve students' learning outcomes and their engagement in the classroom. Further research is needed to extend the understanding of the influence of learning methods on student learning outcomes with a wider scope.